Pemberian Buah Kurma Terhadap Peningkatan Kadar Hemoglobin Pada Remaja Putri - Lathifah, Neneng Siti; Utami, Vida Wira (Universitas Malahayati Bandar Lampung, 2022)
Background The incidence of anemia is a problem most commonly found in young women. Based on the health profile of Lampung Selatan district in 2018, the prevalence of anemia in South Lampung in 2018, as much as 27.9% anemia in young women, in Rangai Tritunggal Village itself in 2018 there were 16 girls who had anemia.Purpose To determine the effect of giving dates to increase hemoglobin levels in anemic adolescent girls in Rangai Tritunggal Keacamatan Katibung Village, South Lampung Regency in 2020.Methods In this study, using a Quasy Experimental research type with a Pre-Post Test With Control design approach. Sampling using purposive sampling. The sample consisted of 22 people, 11 people for the treatment group and 11 people for the control group. Data analysis using paired t-test.Result Based on the results of the study, the difference in the average increase in Hb levels between the pre-test and post-test, in the experimental group was -1.3273gr / dl, was greater than the difference in the average increase in Hb levels in the control group, namely 0.2818gr / dl. using the Paired t-test statistical test showed the value of Sig. (2-tailed) 0.000 <0.05 means that there is an effect of giving dates on an increase in hemoglobin levels in young women with anemia in Rangai Tritunggal Village, South Lampung Regency in 2020.Conclusion There is an effect of giving dates on an increase in hemoglobin levels in anemic adolescent girls in Rangai Tritunggal village. Katibung Sub-district, South Lampung Regency in 2020.Suggestion can be used as input, evaluation and consideration to formulate or create new policies or programs in an effort to improve quality services for young women Keywords : Anemia, Hemoglobin, Palms , Teenagers ABSTRAK Latar Belakang Kejadian anemia merupakan masalah yang paling banyak ditemukan pada remaja putri. Berdasarkan profil kesehatan kabupaten lampung selatan tahun 2018, prevalensi anemia di Lampung selatan pada Tahun 2018,sebanyak 27,9% anemia pada remaja putri, di Desa Rangai Tritunggal sendiri pada tahun 2018 sebanyak 16 remaja putri yang mengalami anemia. Tujuan Untuk mengetahui pengaruh pemberian buah kurma terhadap peningkatan kadar Haemoglobin pada remaja putri anemia di Desa Rangai Tritunggal Keacamatan Katibung Kabupaten Lampung Selatan Tahun 2020.Metode Pada penelitian ini menggunakan jenis penelitian Quasy Eksperimental dengan pendekatan Pre-Post Test With Control desain. Pengambilan sampel menggunakan purposive sampling. Sampel berjumlah 22 orang 11 orang untuk kelompok perlakuan dan 11 orang untuk kelompok kontrol. Analisa data dengan menggunakan uji paired t-test.Hasil Berdasarkan hasil penelitian selisih rata-rata peningkatan kadar Hb antara pre-test dan post-test, pada kelompok eksperimen yaitu -1,3273gr/dl lebih besar daripada selisih rata-rata peningkatan kadar Hb pada kelompok kontrol yaitu 0.2818gr/dl.Hasil penelitian menggunakan uji statistic Paired t-test menunjukkan nilai Sig. (2-tailed) 0.000 < 0.05 artinya ada pengaruh pemberian buah kurma terhadap peningkatan kadar hemoglobin pada Remaja Putri Anemia di Desa Rangai Tritunggal Kabupaten Lampung Selatan Tahun 2020.Kesimpulan Ada pengaruh pemberian buah kurma terhadap peningkatan kadar hemoglobin pada remaja putri anemia di desa Rangai Tritunggal Kecamatn Katibung Kabupaten Lampung Selatan Tahun 2020.Saran dapat digunakan sebagai bahan masukan, evaluasi dan pertimbangan untuk menyusun atau membuat kebijakan atau program baru dalam upaya peningkatan pelayanan pada remaja putri yang berkualitas Kata Kunci : Anemia, Buah Kurma ,Hemoglobin, Remaja